Usability Evaluation of The Interactive 3D Virtual Reality Cultural Heritage Museum Display: Fountain of The Lions Software Application - G., J; ., Tromp; Wolff, A; C. Torres, J; Thi My, Hoang (International Journal of Engineering and Technology, 2018)
In this usability evaluation of the Fountain of the Lions software application aimed to be used by museum visitors, the software is analysed using three established usability research methods: personas, a cognitive walkthrough (task analysis) with three participants, and an individual heuristic evaluation. Areas in which the software succeeds and areas which could use improvement are discussed based on the results of these analyses, including use of the methods.Â